Analysis of gaming actions of the central blocking in competitive activity of women's volleyball amateur teams - Стрельникова, Євгенія; Мельник, Аліна; Ляхова, Тамара (Slobozhanskyi Herald of Science and Sport, 2018)
Ievgeniia Strelnykova, Alina Mel’nik & Tamara Liakhova Purpose: determine the quantitative indicators of the game actions of the central blocking amateur teams in competitions under the aegis Volleyball Federation of Kharkiv region. Material & Methods: an analysis of statistical data obtained as a result of pedagogical observations of the execution of blocks in 36 games (116 games) by 10 players of this role was carried out. The following methods were used: analysis of scientific methodological literature; pedagogical observation, methods of mathematical statistics. Results: quantitative indicators of gaming actions of players related to the execution of blocks, in particular, the distribution of loading of game zones by attacks, the distribution of the number of blocks of different species by zones, the distribution of the number of fines of their attackers are determined. The evaluation of the effectiveness of the actions of the players during blocking in various defense zones was carried out. Conclusions: the results can be used to solve the problem of increasing the effectiveness of the game of central blocking volleyball teams in the process of training and competition.